Evaluasi Program Pembinaan Prestasi Bulutangkis di Klub Persatuan Bulutangkis Jaya Mandiri - Hengky Remora; Rais Firlando (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2020)
This study aims to: 1) evaluate the background and objectives of the coaching program, 2) evaluate human resources, infrastructure and funds, 3) evaluate program implementation, coordination, 4) evaluate the results achieved and welfare This research is a survey research using evaluation the CIPP model program. The research subjects included administrators, coaches, athletes, parents of athletes, the community around the club. The technique of collecting data through 3 ways, namely by (1) interviews, (2) observation (3) documentation. The source of the data studied was the PB Jaya Madiri club, Lubuklinggau City, South Sumatra Province. The analysis technique used is qualitative data analysis with four stages: data collection, data reduction, data presentation, drawing conclusions. The results of this study are 1) the badminton sport coaching carried out by the club is in accordance with the background and program objectives. 2) badminton sports coaching in the club has good and quality human resources, supported by infrastructure and insufficient funds, 3) badminton coaching in clubs which consists of aspects of program implementation and coordination is running well. 4) badminton coaching in the club is a result of the decreasing achievements achieved by athletes, while the welfare category is less. In conclusion, the badminton sport coaching carried out by PB Jaya Mandiri club is appropriate, has good and quality human resources (HR), supported by the availability of adequate infrastructure but limited funds that reduce the achievement of PB Jaya Mandiri club. Keywords: Badminton, Evaluation, Coaching, Programs